TINGKAT PRODUKTIVITAS PRIMER FITOPLANKTON DI SUNGAI ULAR KABUPATEN DELI SERDANG The Grade of Primary Productivity of Phytoplankton in Ular River At Deli Serdang - Eva Christina S; Hesti Wahyuningsih; Tajudddin Siregar (AQUACOASTMARINE, 2015)
The research about primary productivity is a common research, it is because by knowing the value about primary productivity that have by the ecosystem, we know the grade of productivity so we can using naturally and sustainable. The research was done in June until August 2014. The aim of this research was to knowing the grade of Primary Productivity of phytoplankton in Ular River at Deli Serdang and to analyze its relationship with the physical and chemical factors. The sampling station was determinated by Purposive sampling method. Samples were collected from 3 sampling station. The primary productivity was measured by the Oxygen method.The result showed that of primary productivity range from 225,216 – 394.128 mgC/m3/day with the highest value at station 2 and the lowest value at station 1. Analysis of pearson correlation Show that the factors which have a very strong relationship with the primary productivity are abundance of phytoplankton, nitrate, DO and light penetration. Factor which has a strong relationship with pimary productivity is pH.Key Words: primary productivity, oxygen methode , phytoplankton.